Socioeconomic disparities in dietary diversity among adults in Bengbu, China: unraveling the mediating role of nutrition literacy - Sun, Yuhui; Hu, Xiaoting; Tian, Xi; Liu, Huaqing (Frontiers in Nutrition, 2025)
BackgroundSocioeconomic status (SES) was linked to dietary diversity and nutrition literacy (NL) was associated with food choices. This study aims to investigate the association of NL with SES and dietary diversity, and to assess its potential mediating role between SES and dietary diversity among Chinese adults.MethodsA cross-sectional survey was previously conducted in Bengbu, China, including 2,208 adults aged ≥18. SES was primarily measured according to education level and monthly income. Dietary diversity scores (DDS) were collected through a simplified diet frequency questionnaire. NL was evaluated through a twelve-item short-form NL scale. Multiple linear regression and Hayes’ PROCESS framework were used for analysis.ResultsSignificant education- and monthly income-based disparities in dietary diversity were observed (both p < 0.001). After adjusting for confounding factors, each one-unit increase in education and monthly income was associated with a significant 0.29-point (95% confidence interval (CI): 0.20–0.37) and 0.22-point (95% CI: 0.13–0.30) increase in DDS, respectively, and with a 3.25-point (95% CI: 2.79–3.71) and 1.44-point (95% CI: 0.97–1.92) increase in NL, respectively. NL significantly mediated the association between monthly income or education and DDS (β = 0.180, 95% CI: 0.146–0.216; β = 0.136, 95% CI: 0.107–0.168, respectively).ConclusionSufficient NL can increase dietary diversity and plays a pivotal mediating role in the association between SES and dietary diversity. Intervention strategies should target populations with low SES and inadequate NL to improve dietary diversity and reduce economic inequalities in health.